ESTIMASI UMUR GURITA (Octopus cyanea) DI KECAMATAN PRINGGABAYA DAN POTO TANO MENGGUNAKAN METODE STYLET INCREMENT ANALYSIS (SIA) - Rufiati, Indah; Mahardika, I Gede; Wijana, Made Sara (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024), 2024)
Octopus cyanea can be found in coral reef habitats and is an important and potential species for Indonesia. As other species near coastal areas began to decline, octopus became an important source of livelihood for small-scale fishers. Despite its considerable social and economic importance and the high value of octopus exports, Indonesia has no management plan for octopus fisheries. This research aims to estimate the age of an octopus using the incremental stylet analysis method by counting the growth rings in the stylet (reduced shell inside the octopus's head). Data was taken from 3 villages: Poto Tano, Ketapang and Seruni Mumbul, Pringgabaya District, East Lombok Regency, West Nusa Tenggara Province and Poto Tano Village, Poto Tano District, West Sumbawa Regency, West Nusa Tenggara Province. A total of 295 octopuses (141 females and 154 males) were sampled and examined for their stylets by cutting them and observing them with a microscope to calculate the growth rings. The male octopuses observed were between 41 – 176 days old with an average age of 94 days while the female octopus observed were between 41 – 176 days old with an average age of 92 days. The weight when 50% of the population begins to mature is based on analysis using a linear growth model, female octopus begin to mature at a weight of 2,025 grams, while male octopus begin to mature at a weight of 1,804 grams. The smallest adult female octopus was found at 600 grams, while the smallest adult male octopus was found at 400 grams. Keywords: Small-scale fishers; coastal areas; growth rings; octopus weight